Visual Evaluation of the Soil Structure under Different Management Systems in Lowlands in Southern Brazil - Tuchtenhagen,Ivana Kruger (2018)
ABSTRACT The “Visual Evaluation of Soil Structure” (VESS) is a method used primarily to evaluate the soil structural quality of Oxisols in Brazil and secondly for more specific research, consultancy, and teaching purposes. Since the methodology was never applied and compared with laboratory evaluations of physical properties of hydromorphic soils of the Pampa biome in the south of Brazil, this study evaluated the use of VESS as a visual indicator of the structure quality of a typic eutrophic Albaqualf soil under native grassland, crop-livestock integration, no-tillage, and conventional management systems. Experimental areas with these different management systems were subjected to visual (VESS) and laboratory evaluation of the soil structure. The laboratory evaluation was based on traditional methods and on measurements of bulk density, porosity, aggregate mean weight diameter, aggregate tensile strength (ATS), and total organic carbon (TOC). It was concluded that VESS was efficient in differentiating the management system. The management systems based on minimum soil disturbance and mulching with crop residues improved the soil quality, as evidenced by the VESS scores, bulk density, porosity, aggregation, and organic carbon. The TOC content was inversely related with ATS. The quality of a typic eutrophic Albaqualf was benefitted by organic matter in the surface layer.